(untitled) (Global Journal of Medical Research, 2024)
BackgroundË The article analyzes the possibilities of increasing the efficiency of cultural bacteriological testing in patients with infective endocarditis by inoculating arterial and venous blood. MethodsË To substantiate the significance of the proposed combination, the experiments were conducted on 18 dogs to study the difference in the bacterial load between the arterial and venous blood. The experiments included standardized blood cultures and injections of the bacterial suspension of S. aureus isolates cultured in agar plates containing 131 I-labeled albumin. In the arterial and venous blood samples, the relative concentration of 131I was determined by recording counts per minute in the well counter chamber. A total of 141 surgical patients with infectious endocarditis (IE) had venous and arterial blood cultures performed to assess the positive test rates compared to the intraoperative results.